2008
DOI: 10.1016/j.neurobiolaging.2007.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aging and caloric restriction on dentate gyrus synapses and glutamate receptor subunits

Abstract: Caloric restriction (CR) attenuates aging-related degenerative processes throughout the body. It is less clear, however, whether CR has a similar effect in the brain, particularly in the hippocampus, an area important for learning and memory processes that often are compromised in aging. In order to evaluate the effect of CR on synapses across lifespan, we quantified synapses stereologically in the middle molecular layer of the dentate gyrus (DG) of young, middle aged and old Fischer 344 x Brown Norway rats fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
41
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 82 publications
(125 reference statements)
8
41
0
Order By: Relevance
“…We chose a strain of rats with known age-related biological changes in the brain [4][5][6]12,25] and a delay period for the novel object recognition task based on studies in which there are age-related deficits in the novel object recognition task [19,26]. Surprisingly our results demonstrated that there was no difference in young and aged rats in the time spent exploring the novel object.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…We chose a strain of rats with known age-related biological changes in the brain [4][5][6]12,25] and a delay period for the novel object recognition task based on studies in which there are age-related deficits in the novel object recognition task [19,26]. Surprisingly our results demonstrated that there was no difference in young and aged rats in the time spent exploring the novel object.…”
Section: Discussionmentioning
confidence: 88%
“…Thus, in the present study we examined the novel object recognition task at a delay period that has been shown to be impaired in aged rats of two different strains [19,23]. Moreover, we used a strain of rats, F344XBrown Norway, which have published agerelated biological changes in the brain [4][5][6]15,25]. Our data suggest that novel object recognition is not impaired in aged rats although both young and old rats have a demonstrated side preference for the location of the novel object.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations